2023
DOI: 10.1021/acsbiomaterials.2c01059
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Deformability of Breast Cells Analyzed from Patients with Malignant and Benign Breast Diseases

Abstract: Breast cancer is a heterogeneous and dynamic disease, in which cancer cells are highly responsive to alterations in the microenvironment. Today, conventional methods of detecting cancer give a rather static image of the condition of the disease, so dynamic properties such as invasiveness and metastasis are difficult to capture. In this study, conventional molecular-level evaluations of the patients with breast adenocarcinoma were combined with in vitro methods on micropatterned poly(methyl methacrylate) (PMMA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…The interaction between cells and materials is a fundamental issue in the fields of biomaterials and tissue regeneration. Micropillar arrays provide a unique kind of topological surfaces to regulate cell-material interactions. Cell nuclei undergo severe deformation on micropillar arrays with an appropriate dimension, which influenced cell behaviors . Nuclear deformation can also cause chromatin condensation and chromosome relocalization within the nucleus and alter gene expression of the cells. It has been demonstrated that actomyosin and microtubule may synergistically regulate nuclear deformation and chromatin remodeling, finally modulating gene expression .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between cells and materials is a fundamental issue in the fields of biomaterials and tissue regeneration. Micropillar arrays provide a unique kind of topological surfaces to regulate cell-material interactions. Cell nuclei undergo severe deformation on micropillar arrays with an appropriate dimension, which influenced cell behaviors . Nuclear deformation can also cause chromatin condensation and chromosome relocalization within the nucleus and alter gene expression of the cells. It has been demonstrated that actomyosin and microtubule may synergistically regulate nuclear deformation and chromatin remodeling, finally modulating gene expression .…”
Section: Discussionmentioning
confidence: 99%